Clinicopathologic Features of a Series of Primary Renal CIC-rearranged Sarcomas With Comprehensive Molecular Analysis. (October 2018) - Mangray, Shamlal; Kelly, David R.; LeGuellec, Sophie; Fridman, Eddie; Aggarwal, Sangeeta; Shago, Mary; Matoso, Andres; Madison, Russell; Pramanik, Sharmila; Zhong, Shan; Li, Rong; Lombardo, Kara A.; et al.
Abstract : CIC- rearranged sarcomas rarely occur in visceral organs including the kidney. The most common fusion partner with CIC is the DUX4 gene, but variant fusion partners have also been reported. Herein, we describe the clinicopathologic features and comprehensive molecular profiling of 4 cases of primary renal CIC- rearranged sarcomas. All cases occurred in females, age range 13 to 82 years and included 3 resections and 1 needle biopsy specimen. There was a tendency for development of metastatic disease predominantly to the lungs and poor disease outcome despite different treatment strategies. Histologically, variable round cell (20% to 100%), spindle cell (0% to 80%), and rhabdoid morphologies (0% to 20%) were seen. By immunohistochemistry diffuse WT1 nuclear (2 to 3+, ∼90%) labeling was present in 1 case, with cytoplasmic staining in the others (3+, 40% to 75%). CD99 was focally positive in all 4 cases (⩽10%); 1 case each was diffusely positive for c-myc (2 to 3+, ∼90%) and ETV4 (3+, ∼90%); 1 case was focally positive for c-myc (2+, ∼5%) and calretinin (2+, ∼5%); and all cases were negative for cytokeratin and NKX2.2. CIC rearrangement by fluorescence in situ hybridization was present in the 3 cases tested. Comprehensive genomic profiling (CGP) of 3 cases revealed a CIC-DUX4 fusion in 2 cases, and 1 CIC-NUTM1 fusion. All 4 CIC -rearranged renal sarcomas had low mutation burden, and except HLA-A and MLL mutations lacked genomic alterations in other oncogenic drivers. Material from the needle biopsy was insufficient for CGP but that case was positive with the DUX4 immunohistochemical stain as were the 2 CIC-DUX4 tumors. In conclusion, CIC- rearranged sarcomas rarely occur in the kidney with a tendency for poor outcome and in this series we illustrate an example with CIC-NUTM1 fusion, an emerging variant, at a visceral site. Testing by fluorescence in situ hybridization or CGP is optimal to avoid missing cases that harbor variant fusion partners. Abstract : Supplemental Digital Content is available in the text.